COMPARAÇÃO DA ESTIMULAÇÃO ELÉTRICA TRANSCUTÂNEA DO NERVO TIBIAL VERSUS PARASSACRAL EM ADULTOS COM INCONTINÊCIA URINÁRIA DE URGÊNCIA (REMUNOM, 2024)
INTRODUCTION: Urinary incontinence (UI) is the involuntary loss of urine, affecting quality of life and requiring specialized treatment. Transcutaneous electrical stimulation is a physiotherapeutic approach that uses low-intensity currents to improve neuromuscular function. OBJECTIVES: To compare the efficacy of transcutaneous electrical stimulation of the tibial nerve and parasacral stimulation in the treatment of adults with urge urinary incontinence. METHODOLOGY: This is an integrative review of the literature conducted in the PubMed, Scielo and BVS databases, using the descriptors “Transcutaneous Electric Nerve Stimulation” and “Urinary Incontinence”, registered in DeCS/MeSH, associated by the Boolean operator AND. Randomized clinical trials from the last five years, in Portuguese or English, with adults over 18 years of age were included. Duplicate studies, research protocols, and those not related to urinary incontinence or that did not meet the inclusion criteria were excluded. RESULTS AND DISCUSSION: A total of 89 studies were identified through the applied methodology and, after applying the inclusion and exclusion criteria, 4 articles were included for final analysis. The studies discuss the application of tibial and parasacral electrostimulation methods, thus agreeing that the application provides benefits in reducing urinary urgency, with parasacral electrostimulation being superior; however, the effects are not visible in patients with cognitive problems and dependents. CONCLUSION: After comparing both interventions, it is possible to conclude that both techniques provide better results in reducing urinary urgency; however, parasacral electrostimulation was superior in improving quality of life during and after treatment.